Fe3O4/RGO composites for the indigo carmine photo-Fenton discoloration - Gonçalves, Arthur Henrique Azevedo (2023)
Textile Industry plays an important role both in Brazil and the world. However, it is responsible for generate large quantities of synthetic dye-containing effluents. It is well known that many of these dyes are stable when released in the nature. One example is indigo carmine (IC), used worldwide in denim fabrication. This dye is toxic, harmful to human health, and causes serious environmental impacts. Thus, the development of new technologies aiming to treat textile dye-containing effluents it is of great importance. In this work, nanocomposites of magnetite (Fe3O4) anchored on reduced graphene oxide (RGO) were synthesized an evaluated in the IC photo-Fenton discoloration, an advanced oxidative process, considered one of the most promising effluent treatment approaches. Different physicochemical characterization techniques showed that magnetite nanoparticles were successfully anchored on RGO sheets. Besides, the presence of RGO is responsible for improving magnetite properties, yielding to high active materials for IC discoloration. Also, the magnetic properties of these materials provided a simple separation method from the reaction medium. Reuse tests were conducted with the nanocomposite with the best performance showing that it can be used for, at least, 4 cycles, without significant activity loss.